Childhood disablement and family incomes. Issue 3 (September 1983) - Baldwin, S; Godfrey, C; Staden, F
Abstract : Data on the incomes of families with a severely disabled child were obtained by replicating the Family Expenditure Survey. These data were compared with income data from a control group of families with children, drawn from the FES for the same period. The participation rates, hours, and earnings of the women with a disabled child were all found to be substantially lower than those of women in the control group, differences between the samples increasing with the age of the youngest child. The earnings of men with a disabled child were also lower than those of men in the control group, though differences were more pronounced among non-manual workers. Loss of parental earnings was not made good by social security benefits paid on account of disablement. In general the incomes of the families with a disabled child were lower than those of the control families, the magnitude of the differences increasing with family income and the age of the youngest child. Nevertheless, one group of families with a disabled child–manual workers whose youngest child was under 5–had slightly higher incomes than similar families in the control group.